The anti-anxiety/depression effect of a combined complex of casein hydrolysate and γ-aminobutyric acid on C57BL/6 mice - Cai, Lei; Tao, Qian; Li, Wenzhi; Zhu, Xiping; Cui, Chun (Frontiers in Nutrition, 2022)
In view of a series of adverse side effects of drugs for anxiety/depression on the market at present, it is imminent to extract and develop novel anti-anxiety and depression drugs from plants and proteins (like casein hydrolysate) as adjuncts or substitutes for existing anti-anxiety and depression drugs. Consequently, this study investigated the improvement of the anxiety/depression function by the compound of casein hydrolysate and γ-aminobutyric acid (GABA) (casein hydrolysate: GABA = 4:1; CCHAA) on mice induced by chronic restraint stress-corticosterone injection. Animal experiments revealed that oral gavage administration of CCHAA significantly reversed the anxiety/depression-like behaviors. Compared to the model control group, body weights were increased after treatment with CCHAA groups [1.5, 0.75 mg/(g⋅d)]. As a diagnostic index of anxiety and depression, we assessed GABA and 5-HT levels in response to CCHAA ingestion. The GABA and 5-HT levels were increasingly enhanced by the CCHAA diet. In addition, histopathological changes in the hippocampus CA3 region of the anxious/depressed mice were also alleviated after the treatment with the CCHAA. Thus, the casein hydrolysate and GABA formula diets may induce beneficial effects on the mice with anxiety/depression.